Pengaruh Marketing Communication dan Market Orientation Terhadap Competitive Advantage Melalui Product Innovation Sebagai Variabel Mediasi - Fatham Mubina Winangun; Sidiq Permono Nugroho (Economic Reviews Journal, 2025)
This study aims to examine the effect of marketing communication and market orientation on competitive advantage, with product innovation as a mediating variable, especially in MSMEs in Tasikmalaya City. The method used in this research is quantitative, by taking a sample of 100 MSMEs selected through purposive sampling techniques in the area. Data analysis was carried out using Partial Least Square (PLS) techniques assisted by the SmartPLS 3.0 application. The results showed that marketing communication, market orientation, and product innovation have a significant influence on competitive advantage.